Energy Transition of Fishing Fleets: Opportunities and Challenges for Developing Countries - UN Trade; Development (United Nations, 2024)
The review of NDCs conducted in this study shows surprising results. It reveals that major aquatic food exporters, i.e., India, the Kingdom of the Netherlands and Norway show no commitments on ocean or fisheries-related matters. In contrast, Canada, Chile and the Russian Federation have committed to protecting ocean space and include climate mitigation and adaptation measures within marine protected areas. And, despite being a part of the most polluting region in the world, China and Viet Nam stand out for committing to implement measures for energy saving, energy efficiency and emission reduction in fisheries as a means of mitigating GHG emissions. The review of regulations and agreements found little evidence of such measures being used in the fisheries sector.